2007
DOI: 10.1080/01421590701287962
|View full text |Cite
|
Sign up to set email alerts
|

A triangulated approach to the assessment of teaching in childhood epilepsy

Abstract: Seventy per cent of participants rated the lecture on the highest scale for usefulness and interest. There was a significant post-lecture increase in clinical confidence in seizure identification (p < 0.0005). Open-ended questions showed that videos were most useful (81/149) and interesting (109/149), and that the presentation of the syndromal classification provided a useful approach (114/149). Focus group discussion, lecturer and peer observation cross-validated these findings and highlighted the importance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this review seven studies gave no justification for the outcome measure used [13,15,25,26,29,30]. In addition comments by the authors themselves on limitations to the outcome measures were absent in five of the studies [13,26,30,31]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review seven studies gave no justification for the outcome measure used [13,15,25,26,29,30]. In addition comments by the authors themselves on limitations to the outcome measures were absent in five of the studies [13,26,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…In this work both learner knowledge and learner satisfaction were assessed by different measures (a video test, a written test and a course evaluation). Three other studies [14,25,31] had more than one outcome measure, although these were all subtle variations on a theme such as scores in different types of clinical examination in the same test.…”
Section: Discussionmentioning
confidence: 99%
“…Isler et al developed an effective modular epilepsy educational program for medical residents, nurses and EEG technicians. 12 Using a randomized crossover trial of epilepsy education, Bye et al found that although interactive lecturing and a computerized tutorial were both effective, students preferred interactive learning 13 . Bye et al also evaluated medical students’ interest, clinical confidence and perceived usefulness of their epilepsy educational program.…”
Section: Introductionmentioning
confidence: 99%
“…Bye et al also evaluated medical students’ interest, clinical confidence and perceived usefulness of their epilepsy educational program. 13 …”
Section: Introductionmentioning
confidence: 99%